TAKING E-MODERATING SKILLS TO THE NEXT LEVEL: REFLECTING ON THE DESIGN OF CONFERENCING ENVIRONMENTS - Ross, Shelagh M.; Kukulska-Hulme, Agnes; Chappel, Helen; Joyce, Brian (Online Learning, 2004)
This paper reports an analysis of computer conference structures set up for a distance education course in which major components of the teaching and learning involve group discussions and collaboration via asynchronous text-based conferencing. As well as adopting traditional e-moderator roles, tutors were required to design appropriate online spaces and navigation routes for students. Tutors’ views concerning conference structures focussed on tensions between enabling easy access to conference areas, facilitating the successful running of activities, and addressing students’ subsequent needs for retrieval of conference material for assessment tasks. The geographically dispersed course tutors initially explored these issues in reflective online conversations. Comparisons were made between structures that were set up differently but all used for essentially the same tasks and purposes. Evidence from conference messages, from student feedback given in questionnaire and interview responses, as well as from students’ written assignments, provided insights into the impact such structures may have on the student learning experience. Students found conference areas for their own group easy to navigate, but they had concerns about managing the large number of messages; these concerns centred on the volume, threading, linking, length, and language of messages.